The Use of Deixis in Online Classroom Interaction Among the University Students - M. Rizki Giffary; Widhiyanto Widhiyanto (Universitas Negeri Semarang, 2023)
Pragmatics is the study related to linguistics used by a person. It is the study of language and its content. Therefore, it becomes the basis for knowing the meaning of a language. Pragmatics is focused on the investigation of importance as conveyed by the speaker (or author) and deciphered by the audience (or reader). This research aimed to find the use of deixis in online class interaction among the third-semester students of the graduate school Universitas Negeri Semarang 2020/2021, the data of this study were the students' interactions in the WhatsApp application during the class of the graduate school Universitas Negeri Semarang. This research was a form of qualitative research proposed by Creswell (2009). We were required to be able to classify, collect, analyze, and draw conclusions through the phenomena that have been analyzed without making a generalization. The findings showed that from 26 students' discussion results, 1.156 deixes were found in the students’ discussions. Then, the deixis were categorized into five categories based on Levinson’s theory. There were 529 personal deixes that equal to 45.76%, 55 temporal deixes that equal with 4.75%, there are 108 in spatial deixis that equal to 9.34%, 329 in social deixis that equal with 28.46%, and 135 in discoursal deixis that equal to 11.67%. This study in like manner expected to give inspiration for the readers who are intrigued on the deixis study and it will be an additional reference for readers who are intrigued on examining this examination